Using a semi‐conductor sequencing‐based panel for genotyping of HPV‐positive and HPV‐negative oropharyngeal cancer: a retrospective pilot study. (8th January 2017) - Ham, J.C.; Tops, B.B.J.; Driessen, C.M.L.; van Raaij, A.W.M.; Slootweg, P.J.; Melchers, W.J.G.; Ligtenberg, M.J.L.; van Herpen, C.M.L.
Abstract : Objectives: The aim of this study was to assess the feasibility of testing actionable mutations in small amounts of formalin‐fixed paraffin‐embedded material in multiple genes of the receptor tyrosine kinase pathway and to determine the frequency of these mutations in human papillomavirus (HPV)‐positive and HPV‐negative oropharyngeal cancer (OPC). Design: A retrospective pilot study was performed. Setting: In OPC, no predictive markers for response to epidermal growth factor receptor inhibition are known. Therefore, identifying predictive biomarkers is of utmost importance, but is often hampered by the small amount of tumour material available. Participants: We included the archival material of 45 OPC, all treated with concomitant chemoradiotherapy between 2003 and 2010. Main outcome measures: Besides the HPV status, we assessed mutations using a gene panel that targets 16 genes in the receptor tyrosine kinase pathway and six other genes. The polymerase chain reaction required only 10 ng DNA. Results: In total, 42 of the 45 biopsies have been successfully analysed. In total 20 of 42 samples were HPV‐positive and 22 of 42 were HPV‐negative. In the receptor tyrosine kinase pathway, mutations in PIK3CA were most frequently identified. A TP53 mutation was identified in one HPV‐positive sample and in 13 HPV‐negative samples. Additionally, three mutations in three different genes were found. Conclusions: We evaluated an assay to identify mutations in the receptor tyrosine kinase pathway. As only small amounts of formalin‐fixed paraffin‐embedded material are sufficient for reliable analysis, this test opens up new possibilities for personalised medicine.